Pengaruh Likuiditas Dan Pertumbuhan Penjualan Terhadap Struktur Modal - Sistya Racmawati; Yusuf Faisal (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2024)
Purpose – This study aims to see the effect of liquidity and sales growth on the capital structure of mining sector companies Design/methodology/approach – The method used in this study uses quantitative methods by sampling using purposive sampling techniques with the results of 41 mining sector companies listed on the Indonesia Stock Exchange in 2017- 2021. The data used is secondary data, namely data obtained directly in the form of financial statements from www.idx.com sites and their respective company websites which are used as research samples. Data analysis techniques are carried out using statistical analysis, namely: classical assumption tests (normality, multicollinearity, heterokedasticity, and autocorrelation), multiple linear analysis, and hypothesis tests, as well as coefficients of determination with SPSS 25.0 for window. Findings – Based on the results of the study, it was found that liquidity has a negative and insignificant effect on the capital structure, while sales growth has a negative and significant influence on the capital structure of mining sector companies Research limitations/implications – For the conclusions that have been put forward, researchers can provide some suggestions for improving the quality of further research. The suggestions proposed by the researcher include adding the number of other variables that are expected to affect the capital structure, then the company is advised to pay attention to the factors that affect its capital structure